2019
DOI: 10.1002/chem.201904148
|View full text |Cite
|
Sign up to set email alerts
|

Early Main Group Metal Catalysts for Imine Hydrosilylation

Abstract: The efficient catalytic reduction of imines with phenylsilane is achieved by using the potassium, calcium and strontium based catalysts [(DMAT)K (THF)]∞, (DMAT)2Ca⋅(THF)2 and (DMAT)2Sr⋅(THF)2 (DMAT=2‐dimethylamino‐α‐trimethylsilylbenzyl). Eight different aldimines and the ketimine Ph2C=NPh could be successfully reduced by PhSiH3 at temperatures between 25–60 °C with catalyst loadings down to 2.5 mol %. Also, simple amides like KN(SiMe3)2 or Ae[N(SiMe3)2]2 (Ae=Ca, Sr, Ba) catalyze this reaction. Activities incr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 45 publications
0
21
0
Order By: Relevance
“…It has been shown that the sterically moderately encumbered Ae metal bis-amide complexes Ae[N(SiMe 3 ) 2 ] 2 , abbreviated as AeN" 2 (Ae = Ca, Sr, Ba), react in situ with H 2 or PhSiH 3 to large hydride clusters [37,38] that are efficient catalysts for imine or alkene hydrogenation [45][46][47] or hydrosilylation. [48] These studies also showed that, although these systems are less defined, they are highly robust and tolerate higher temperatures. Encouraged by the hydrodehalogenation capability of the well-defined strontium hydride complex [( DIPeP BDI)SrH] 2 , we wondered whether simple amides could also be effective in the activation of the most challenging CÀ F bond.…”
Section: Hydrodefluorination With Undefined Ae Metal Hydride Complexesmentioning
confidence: 99%
“…It has been shown that the sterically moderately encumbered Ae metal bis-amide complexes Ae[N(SiMe 3 ) 2 ] 2 , abbreviated as AeN" 2 (Ae = Ca, Sr, Ba), react in situ with H 2 or PhSiH 3 to large hydride clusters [37,38] that are efficient catalysts for imine or alkene hydrogenation [45][46][47] or hydrosilylation. [48] These studies also showed that, although these systems are less defined, they are highly robust and tolerate higher temperatures. Encouraged by the hydrodehalogenation capability of the well-defined strontium hydride complex [( DIPeP BDI)SrH] 2 , we wondered whether simple amides could also be effective in the activation of the most challenging CÀ F bond.…”
Section: Hydrodefluorination With Undefined Ae Metal Hydride Complexesmentioning
confidence: 99%
“…[98] Their optimisation study revealed the silane has an influence on reactiont ime, where PhSiH 3 was the most active however Et 3 SiH was selected due to tertiary silanes being industrially relevant.T his area has only seen further development in 2019 from Hardera nd co-workers reporting the successful reduction of imines via hydrosilylatione mploying potassium, calcium and strontium2 -dimethyl-amino-a-trimethylsilylbenzyl (DMAT) pre-catalystsa longside simple amide MHMDS( M= Ba, Sr,C a, K) pre-catalysts (Figure 4). [99] The DMAT catalysts displayed enhanced reactivityh ence these were discussed in more detail. Ar eactivity profile was observedw here Sr > Ca > K, highlighting the importance of the Lewis acidity in Group 2m etals.Solventchoice also influenced reactivity where C 6 D 6 was optimum, as tetrahydrofuran (THF) competes with imine precoordination for substrate activation.…”
Section: Catalytic Hydrosilylation Of Iminesmentioning
confidence: 97%
“…This area has only seen further development in 2019 from Harder and co‐workers reporting the successful reduction of imines via hydrosilylation employing potassium, calcium and strontium 2‐dimethyl‐amino‐α‐trimethylsilylbenzyl (DMAT) pre‐catalysts alongside simple amide MHMDS (M=Ba, Sr, Ca, K) pre‐catalysts (Figure 4). [99] The DMAT catalysts displayed enhanced reactivity hence these were discussed in more detail. A reactivity profile was observed where Sr>Ca>K, highlighting the importance of the Lewis acidity in Group 2 metals.…”
Section: Catalysismentioning
confidence: 99%
“…Harder and co-workers reported that potassium, calcium, strontium and barium-based catalysts can be used for an efficient reduction of imines. 80,81 Notably, the authors showed that the incorporation of well-defined ligands is not necessary, and Si-H bonds might be easily activated by simple amides such as alkali and alkaline earth metal bis(trimethylsilyl) amides. One amongst them is easy to use potassium hexamethyldisilazide, which is commercially available.…”
Section: Hydrosilylation Of Unsaturated Carbon-heteroatom (O N) Moiementioning
confidence: 99%
“…Certainly, the discoveries done by the pioneers such as Harder, Hill, Okuda, and Sadow might be brought forward here. [80][81][82][83][84][85][86][87][88] They are less sustainable, and the installation of special ligands requires a number of steps, during which undesired wastes are generated. In this respect, it should however be noted that such research investigations are extremely interesting and provide a wide range of theoretical answers that may have an impact on practical approaches, especially in order to ensure high selectivity for the synthesis of fine chemicals.…”
Section: Hydrosilylation Of Unsaturated Carbon-heteroatom (O N) Moiementioning
confidence: 99%